2001
DOI: 10.1053/jhep.2001.27948
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary thrombophilia as a cause of Budd-Chiari syndrome: A study from Western India

Abstract: The inherited deficiencies of protein C, protein S, antithrombin III, factor V Leiden mutation, prothrombin gene polymorphism, and antiphospholipids were studied in 53 Budd-Chiari syndrome (BCS) and 33 portal vein thrombosis (PVT) cases and compared with 223 age-and sex-matched controls. Protein C deficiency was detected in 7 (13.2%), protein S in 3 (5.7%), and antithrombin III in 2 (3.8%) of the BCS cases. Factor V Leiden was the most common risk factor, i.e., 14 of 53 (26.4%) in BCS cases followed by protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
97
3
6

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(111 citation statements)
references
References 31 publications
5
97
3
6
Order By: Relevance
“…All previous Indian series, except two [29,32] , describe the predominance of IVC up to 79.2% [7,9,[11][12][13]15,30,39,40,42] or IVC-HV obstruction up to 57.7% [14,24,25,35] ; HV involvement was described in 0%-32% of cases in these series [7,9,[11][12][13][14][15]24,25,30,35,39,40,42] . Of the two distinct previous series, one (total 53 cases) showed similar frequency of HV (35.8%), IVC (33.9%) and combined IVC-HV involvement (30.1%) [29] ; whereas the other series involving only chronic BCS showed predominance of HV (45.9%) followed by combined IVC-HV (29.7%) and IVC involvement (24.3%) [32] . In the western countries, hepatic vein thrombosis remains responsible for majority of BCS cases, IVC obstruction is rarely found.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…All previous Indian series, except two [29,32] , describe the predominance of IVC up to 79.2% [7,9,[11][12][13]15,30,39,40,42] or IVC-HV obstruction up to 57.7% [14,24,25,35] ; HV involvement was described in 0%-32% of cases in these series [7,9,[11][12][13][14][15]24,25,30,35,39,40,42] . Of the two distinct previous series, one (total 53 cases) showed similar frequency of HV (35.8%), IVC (33.9%) and combined IVC-HV involvement (30.1%) [29] ; whereas the other series involving only chronic BCS showed predominance of HV (45.9%) followed by combined IVC-HV (29.7%) and IVC involvement (24.3%) [32] . In the western countries, hepatic vein thrombosis remains responsible for majority of BCS cases, IVC obstruction is rarely found.…”
Section: Discussionmentioning
confidence: 90%
“…Previously, MOVC was thought to be the predominant cause of IVC involvement (20.4%-58.6%) and of BCS in India [6,7,[11][12][13][14][15]17,29,35,39] , as well as in Asian countries [49,50,53] . In two recent Indian studies, MOVC was present in 0% and 17.2%, while IVC involvement was seen in 56.2% and 62% cases, respectively [24,40] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Protein C deficiency is seen in 8-9%, protein S deficiency in 3-4%, factor V Leiden mutation in 3-6% and antiphospholipid antibody in 18-23%. 11,[33][34][35] Antithrombin III deficiency and prothrombin gene mutation are however uncommon. However another study from India of 26 PVT patients showed the presence of protein C deficiency in 12, protein S deficiency in 9, antithrombin III deficiency in 8 patients, ACLA in 3 and LA in 4 patients.…”
Section: Inherited Prothrombotic Disordersmentioning
confidence: 99%